Flavin-Based Electron Bifurcation, Ferredoxin, Flavodoxin, and Anaerobic Respiration With Protons (Ech) or NAD+ (Rnf) as Electron Acceptors: A Historical Review - Buckel, Wolfgang; Thauer, Rudolf K. (Frontiers in Microbiology, 2018)
Flavin-based electron bifurcation is a newly discovered mechanism, by which a hydride electron pair from NAD(P)H, coenzyme F420H2, H2, or formate is split by flavoproteins into one electron with a more negative redox potential and one with a more positive redox potential than that of the electron pair. Via this mechanism microorganisms generate low potential electrons for the reduction of ferredoxins (Fd) and flavodoxins (Fld). The first example was described in 2008 when it was found that the butyryl-CoA dehydrogenase-electron-transferring flavoprotein complex (Bcd-EtfAB) of Clostridium kluyveri couples the endergonic reduction of ferredoxin (E0’= −420 mV) with NADH (−320 mV) to the exergonic reduction of crotonyl-CoA to butyryl-CoA (−10 mV) with NADH. The discovery was followed by the finding of an electron-bifurcating Fd- and NAD-dependent [FeFe]-hydrogenase (HydABC) in Thermotoga maritima (2009), Fd-dependent transhydrogenase (NfnAB) in various bacteria and archaea (2010), Fd- and H2-dependent heterodisulfide reductase (MvhADG-HdrABC) in methanogenic archaea (2011), Fd- and NADH-dependent caffeyl-CoA reductase (CarCDE) in Acetobacterium woodii (2013), Fd- and NAD-dependent formate dehydrogenase (HylABC-FdhF2) in Clostridium acidi-urici (2013), Fd- and NADP-dependent [FeFe]-hydrogenase (HytA-E) in Clostridium autoethanogrenum (2013), Fd(?)- and NADH-dependent methylene-tetrahydrofolate reductase (MetFV-HdrABC-MvhD) in Moorella thermoacetica (2014), Fd- and NAD-dependent lactate dehydrogenase (LctBCD) in A. woodii (2015), Fd- and F420H2-dependent heterodisulfide reductase (HdrA2B2C2) in Methanosarcina acetivorans (2017), and Fd- and NADH-dependent ubiquinol reductase (FixABCX) in Azotobacter vinelandii (2017). The electron-bifurcating flavoprotein complexes known to date fall into four groups that have evolved independently, namely those containing EtfAB (CarED, LctCB, FixBA) with bound FAD, a NuoF homologue (HydB, HytB or HylB) harboring FMN, NfnB with bound FAD, or HdrA harboring FAD. All these flavoproteins are cytoplasmic except for the membrane-associated protein FixABCX. The organisms - in which they have been found - are strictly anaerobic microorganisms except for the aerobe A. vinelandii. The electron-bifurcating complexes are involved in a variety of processes such as butyric acid fermentation, methanogenesis, acetogenesis, anaerobic lactate oxidation, dissimilatory sulfate reduction, anaerobic- dearomatization, nitrogen fixation, and CO2 fixation. They contribute to energy conservation via the energy-converting ferredoxin: NAD+ reductase complex Rnf or the energy-converting ferredoxin-dependent hydrogenase complex Ech. This Review describes how this mechanism was discovered.